Caveolae Control Contractile Tension for Epithelia to Eliminate Tumor Cells - Teo, Jessica L.; Gomez, Guillermo A.; Weeratunga, Saroja; Davies, Elizabeth M.; Noordstra, Ivar; Budnar, Srikanth; Katsuno-Kambe, Hiroko; McGrath, Meagan J.; Verma, Suzie; Tomatis, Vanesa; Acharya, Bipul R.; Balasubramaniam, Lakshmi; et al. (Developmental Cell, 2020)
Epithelia are active materials where mechanical tension governs morphogenesis and homeostasis. But how that tension is regulated remains incompletely understood. We now report that caveolae control epithelial tension and show that this is necessary for oncogene-transfected cells to be eliminated by apical extrusion. Depletion of caveolin-1 (CAV1) increased steady-state tensile stresses in epithelial monolayers. As a result, loss of CAV1 in the epithelial cells surrounding oncogene-expressing cells prevented their apical extrusion. Epithelial tension in CAV1-depleted monolayers was increased by cortical contractility at adherens junctions. This reflected a signaling pathway, where elevated levels of phosphoinositide-4,5-bisphosphate (PtdIns(4,5)P2) recruited the formin, FMNL2, to promote F-actin bundling. Steady-state monolayer tension and oncogenic extrusion were restored to CAV1-depleted monolayers when tension was corrected by depleting FMNL2, blocking PtdIns(4,5)P2, or disabling the interaction between FMNL2 and PtdIns(4,5)P2. Thus, caveolae can regulate active mechanical tension for epithelial homeostasis by controlling lipid signaling to the actin cytoskeleton.
CRIS-Team Scopus Importer:2024-02-19
Keywords: actomyosin; caveolae; epithelial tension; extrusion; phosphoinositides